Forgetful but not forgotten: Bathroom‐related craniofacial trauma among the elderly. (14th July 2016) - Hanba, Curtis; Gupta, Amar; Svider, Peter F.; Folbe, Adam J.; Eloy, Jean Anderson; Zuliani, Giancarlo F.; Carron, Michael A.
Abstract : Objectives/Hypothesis: As our population ages, injuries attributable to falls continue to increase, impacting healthcare delivery. Evaluation of craniofacial trauma with focus on elderly patients remains an underappreciated concern. Our objectives were to evaluate injury trends associated with elderly bathroom falls, as this information may be useful for counseling and preventive purposes. Study Design: Database review. Methods: The National Electronic Injury Surveillance System was evaluated for craniofacial trauma among patients 60 years and older presenting to the emergency department (ED) (2010–2014). Injury descriptions were reviewed for mechanism of injury, patient demographics, and other injury characteristics. Results: In total, 7.2% of the estimated 3.4 million ED visits for elderly craniofacial trauma were bathroom related. Females comprised the majority (60.9%) of patients, and a plurality of patients were in their 80s. A greater proportion of facial injuries resulted from syncope (16.6% vs. 10.9% compared to head injuries). Toilets facilitated a greater proportion of facial insults and were more likely to require admission; the most common mechanism was "falling off." Showers contributed a majority of head injuries and had a lower median age than toilet injuries. Fractures comprised 12.6% of facial injuries; of craniofacial fractures, common sites included the nose (54%), mandible (6%), and orbit (6%). Admitted patients were significantly older than those who were released. Conclusions: Bathroom falls result in a significant proportion of elderly traumatic injury. The trends we present offer the opportunity for targeted preventative measures to decrease the occurrence of these events. Additionally, this information may adjunct a detailed history and physical to ensure appropriate patient management. Level of Evidence: 4 Laryngoscope, 127:820–827, 2017